PENGARUH PERCEIVED VALUE TERHADAP REVISIT INTENTION PADA KAWASAN EKOWISATA MANGROVE PANTAI INDAH KAPUK - Icca Frensia Renaldo; Dewanta Facrureza (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the effect of perceived value on revisit intention among visitors to the Mangrove Ecotourism Area Pantai Indah Kapuk, North Jakarta. Perceived value in this study refers to visitors overall perception of the benefits received relative to the sacrifices made, including monetary costs, time, and effort, during the ecotourism experience. Revisit intention refers to visitors intentions to return to the destination or recommend it to others in the future. This study employed a quantitative approach with a descriptive-analytic design. A purposive sample of 100 respondents was selected from visitors who had previously visited the Mangrove Ecotourism Area Pantai Indah Kapuk and were at least 17 years of age. Data were collected through a structured questionnaire using a 4 point Likert scale and analyzed using validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, T-tests, F-tests, and the coefficient of determination (R²) with IBM SPSS Statistics 26. The results indicate that all five dimensions of perceived value emotional value, social value, functional value, epistemic value, and value for money each have a positive and significant partial effect on revisit intention. Simultaneously, these five dimensions also have a positive and significant combined effect on revisit intention, with an F-value of 29.852 and an Adjusted R Square of 59.3%, indicating that the independent variables explain 59.3% of the variation in revisit intention. These findings offer practical implications for ecotourism managers to improve facility quality, strengthen educational value, optimize emotional experience, and maintain affordable pricing to encourage repeat visits and support destination sustainability.